In vitro Antibacterial Effect of Reduning Combined with Polymyxin on Carbapenem Resistant Klebsiella pneumoniae - Shangguan ZF; Chen HL; Li YF; Shi N; Mao QF (Infection and Drug Resistance)
Zui-Fei Shangguan,1 Hong-Lei Chen,2 Yi-Fan Li,3 Na Shi,4 Qi-Fen Mao2 1Department of Clinical Laboratory, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Chinese Medicine), Hangzhou, Zhejiang, 310006, People’s Republic of China; 2Department of Clinical Laboratory, Tongde Hospital of Zhejiang Province, Hangzhou, Zhejiang, 310012, People’s Republic of China; 3College of Laboratory Medicine and College of Bioengineering, Hangzhou Medical University, Hangzhou, Zhejiang, 311399, People’s Republic of China; 4Medical Laboratory, Second Sanatorium of Air Force Healthcare Center for Special Services, Hangzhou, Zhejiang, 310007, People’s Republic of ChinaCorrespondence: Qi-Fen Mao, Department of Clinical Laboratory, Tongde Hospital of Zhejiang Province, 234#, Gucui Road, Hangzhou, Zhejiang, 310012, People’s Republic of China, Email maoqifen@alu.zcmu.edu.cnObjective: This study aimed to investigate the status of carbapenem-resistant strains of Klebsiella pneumoniae isolated from the Department of Microbiology, Zhejiang Tongde Hospital between September 2023 and February 2024, and to examine the in vitro antibacterial effect of Reduning combined with polymyxin on carbapenem-resistant Klebsiella pneumoniae (CRKP), which may provide evidence on the application of Reduning in the clinical anti-infective therapy.Methods: A total of 50 different isolates of CRKP were collected, and the minimum inhibitory concentrations (MIC) of polymyxin, Reduning and polymyxin plus Reduning were measured with microbroth dilution method. Then, the fractional inhibition concentration index (FICI) was calculated.Results: A total of 50 strains of CRKP were isolated, sputum and clean urine were the most common source of CRKP, and intensive care unit was the most common source department. More than 90% of CRKP strains were resistant to cefepime, ceftazidime, piperacillin/tazobactam, and cefoperazone/sulbactam. The rate of resistance to levofloxacin was high, but that to tobramycin, tigecycline, and compound sulfamethoxazole was low. In addition, MIC of Reduning plus polymyxin for CRKP was lower than that of Reduning or polymyxin alone. Among 50 strains of CRKP, FICI ≤ 0.5 was noted in 7 strains, 0.5 < FICI ≤ 1.0 in 43 strains, and none had FICI > 1.0. The results showed Reduning combined with polymyxin B exerted additive effect on CRKP and conferred synergistic effect on several strains of CRKP.Conclusion: Reduning has antibacterial effect on CRKP in vitro, and the addition of Reduning can reduce the dose of polymyxin in the treatment of CRKP.Keywords: Reduning, polymyxin, Carbapenem resistant Klebsiella pneumoniae, in vitro antibacterial activity